Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/bbb.2110
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic evaluation of a natural deep eutectic solvent‐based biorefinery: Exploring different design scenarios

Abstract: This paper presents a comprehensive techno‐economic evaluation of an integrated natural deep eutectic solvent (NADES)‐based biorefinery – a 1 ton day−1 capacity design plant. The key parameters include payback period, net present value (NPV), and internal rate of return (IRR). These were compared with the parameters of conventional biorefineries. The ‘nth plant’ results clearly revealed that the single product‐based biorefinery is not a sustainable approach. Hence, value‐added products viz., cellulose, lignin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Indeed, Kumar et al demonstrated that, even after vigorous washing of the pretreated biomass with water for removal of the NADES reagent from the biomass residue, a still negligible amount of the NADES reagent was strongly bound to the biomass. Intriguingly, the cellulase activities were found to be increased significantly where the pH of the NADES reagent is close to neutrality, while it decreased in acidic NADES reagents, with a nearly complete loss in enzyme activity after 24-h incubation even in 5% ( v/v ) NADES reagent [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Kumar et al demonstrated that, even after vigorous washing of the pretreated biomass with water for removal of the NADES reagent from the biomass residue, a still negligible amount of the NADES reagent was strongly bound to the biomass. Intriguingly, the cellulase activities were found to be increased significantly where the pH of the NADES reagent is close to neutrality, while it decreased in acidic NADES reagents, with a nearly complete loss in enzyme activity after 24-h incubation even in 5% ( v/v ) NADES reagent [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several recent reviews highlight the potential use of NADESs for biomass pretreatment, [ 40 , 41 , 42 ]; in particular, Kumar et al (2016) [ 43 ] recently demonstrated how hydrophilic NADESs could replace other harsh chemical agents such as hydrochloric acid and sodium hydroxide for pretreatment of lignocellulosic agriresidues.…”
Section: Introductionmentioning
confidence: 99%
“…158 Based on this DES, Kumar et al carried out a technical-economic analysis for a biorefinery process that utilises different types of biomass for the production of cellulose, lignin, and silicates in a plant-and economically viable way. 159 Although the inhibition effect of the LA component of DES was easily overcome by optimising one-pot saccharification pretreatment processes, 156 the remaining problems were more difficult to solve. Replacing LA with other organic acids only partially solved the difficulties described above.…”
Section: Pretreatment Of Biomassmentioning
confidence: 99%
“…This price can rise significantly in the case of low molecular weight native and/or high-purity lignin, thus showing the economic relevance of the above described 'lignin first' processes. 172 Of the industrial-scale pretreatment processes, Organosolv processes are the mildest towards the structure of lignin and thus the most suitable for the 'lignin-first' biorefinery. 173 Although the limitations of such processes have previously been pointed out both economically and environmentally, lignin obtained by Organosolv processes is nowadays the reference material in the lignin field.…”
Section: Ils and Dess For The 'Lignin First' Biorefinery Processmentioning
confidence: 99%
See 1 more Smart Citation